Muhammad Cheng Ho Pasuruan Da’wah Management Picture In Conserving The Mosque: Muhammad Cheng Ho Pasuruan Da’wah Management Picture In Conserving The Mosque - Halimatus, Nur; Astutik, Sri (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2023)
The Muhammad Cheng Ho Mosque is one of the mosques that has a unique architectural form with Chinese characteristics, this mosque is often also called a tourist mosque because many visitors come with offers of strategic places, and there is also a souvenir center and the Cuggrang museum next to it , but it is a challenge for takmir and administrators in managin g the mosque to remain attractive to local residents with residents who can be said to be not so close. So the first question to be answered in this study is